Event‐triggered dynamic surface control of uncertain nonlinear networked systems subject to transmission delays. (5th December 2022) - Karimi, Zahra; Jalali, Ali Akbar; Batmani, Yazdan
Abstract: In this paper, an event‐triggered dynamic surface control technique is proposed for strict‐feedback uncertain nonlinear networked systems in the presence of network‐induced time delays. First, an event‐based dynamic surface control law is designed. Then, by rewriting the control law as a communication‐delay‐distribution‐dependent model, the closed‐loop error dynamics is derived and modeled as a linear time‐delay system with perturbation terms. Next, a periodic event‐triggering condition is designed by imposing some inequality constraints on the perturbations. A theorem related to the H ∞ $$ H_{∞ } $$ ultimate boundedness and quadratic tracking of the closed‐loop system is presented. The proposed technique is utilized to design a decentralized dynamic surface control structure with event‐triggered inter‐vehicle communications for a vehicle platoon.